Añadido a la bibliografía viquiana (1996-2000) Añadido a la bibliografía viquiana (1996-2000) [pp. 193-197]. - Gilbhard, Thomas (Cuadernos sobre Vico, 2020)
Número 19-20, 2006-2007. 470 págs. ISBN 1130-7498